2022
DOI: 10.1002/arch.21874
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial genomes of 10 Mantidae species and their phylogenetic implications

Abstract: This article aims to present a phylogenetic evaluation of Mantidae based on a mitochondrial genome (mitogenome) data set. The mitogenome of 10 Mantidae species were sequenced using next-generation sequencing. The length of nine the complete mitogenomes ranged from 15,371 bp in Tenodera aridifolia to 16,063 bp in Hierodula longa. Mantidae mitogenomes have 37 genes and control region with two exceptions: five trnR copies in Statilia maculata, and H. zhangi was incomplete missing trnI, trnQ, trnM and a portion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Pseudogene trnM* was found at the 3′ end of a large noncoding region (LNCs) between trnM and nad2 in R. longa , R. valida , R. kirbyi , R. latipronotum , R. hyalina sp. nov. , and R. Stalli , which was also reported in seven other Hierodulinae species [ 35 ]. For those nearly complete mitogenomes, the trnI , trnQ, and trnM were not found in H. latipennis , and the trnI and trnQ were not found in R. zhangi , and R. megaera .…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Pseudogene trnM* was found at the 3′ end of a large noncoding region (LNCs) between trnM and nad2 in R. longa , R. valida , R. kirbyi , R. latipronotum , R. hyalina sp. nov. , and R. Stalli , which was also reported in seven other Hierodulinae species [ 35 ]. For those nearly complete mitogenomes, the trnI , trnQ, and trnM were not found in H. latipennis , and the trnI and trnQ were not found in R. zhangi , and R. megaera .…”
Section: Resultssupporting
confidence: 61%
“…Our study did not include the Australasian and Papua lineages such as Tamolanica and the species related to Hierodula majuscula of the Hierodula + Rhombodera complex. However, we conclude that it will not influence the validity of the above discussion because the ancestral position of these lineages [ 35 ] and distinct male genitalia [ 10 ] give this lineage relative independence compared to the oriental lineages.…”
Section: Discussionmentioning
confidence: 95%
“…These species are distributed worldwide, mainly in tropical and subtropical areas, and occupy diverse habitats ranging from tropical rainforests to arid deserts [ 2 , 3 ]. There have been numerous studies exploring the taxonomic status within Mantodea based on morphology or molecular data [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Existing research confirmed the monophyly of the order Mantodea and Mantodea clustered into Dictyoptera with Blattodea [ 4 , 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, both short NCRs and long NCRs (short NCRs ranging from 20 bp to 90 bp and long NCRs over 90 bp) between genes have been widely reported in insects as well as some unique characteristics in several orders or families [ 6 , 18 , 30 , 35 , 44 , 45 , 46 , 47 , 48 , 49 ]. For instance, in Ephemeroptera, trnA -NCR- trnR (with a NCR ranging from 32 to 47 bp) was frequently found in all heptageniid mitogenomes (Ephemeroptera: Heptageniidae) [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these gene rearrangement events, the duplication of trnR within the ND3-A-R-N-S-E-F-ND5 region is the most prevalent. Previous studies have identified a few cases of trnR duplication in cernomantodean lineages, including Gonypetoidea, Haanioidea, Mantoidea, as well as some Eremiaphiloidea and Hymenopoidea [ 22 , 25 , 28 , 40 , 41 ]. Our study identified two additional cases in Amerimantodea, represented by Angela sp.…”
Section: Discussionmentioning
confidence: 99%